2009
DOI: 10.1021/bi9009488
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Large and Small Subunits of Different Acetohydroxyacid Synthase Isozymes of Escherichia coli

Abstract: The large, catalytic subunits (LSUs; ilvB, ilvG and ilvI, respectively) of enterobacterial acetohydroxyacid synthases isozymes (AHAS I, II and III) have molecular weights approximately 60 kDa and are paralogous with a family of other thiamin diphosphate dependent enzymes. The small, regulatory subunits (SSUs) of AHAS I and AHAS III (ilvN and ilvH) are required for valine inhibition, but ilvN and ilvH can only confer valine sensitivity on their own LSUs. AHAS II is valine resistant. The LSUs have only approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…The detailed feedback inhibition of AHAS is described below. A recent study based on the activation of each of the catalytic subunits with each of the regulatory subunits of E. coli isozymes compared the specificity of homologous (catalytic and regulatory subunits of same isozymes) and heterologous (catalytic and regulatory subunits of different isozymes) interactions [45]. It was found that the regulatory subunit of AHAS II can also activate the catalytic subunits of AHAS I and III, and that they also exhibit kinetic parameters similar to those observed in the enzymes reconstituted with the original catalytic and regulatory subunits.…”
Section: Bacterial Ahassmentioning
confidence: 99%
“…The detailed feedback inhibition of AHAS is described below. A recent study based on the activation of each of the catalytic subunits with each of the regulatory subunits of E. coli isozymes compared the specificity of homologous (catalytic and regulatory subunits of same isozymes) and heterologous (catalytic and regulatory subunits of different isozymes) interactions [45]. It was found that the regulatory subunit of AHAS II can also activate the catalytic subunits of AHAS I and III, and that they also exhibit kinetic parameters similar to those observed in the enzymes reconstituted with the original catalytic and regulatory subunits.…”
Section: Bacterial Ahassmentioning
confidence: 99%
“…This is in contrast to AHAS III [10] or, for example, the single AHASs of Mycobacterium avium [18] or Bacillus stearothermophilus [19], which all show noncompetitive partial inhibition by valine. The regulatory subunit (RSU) of AHAS I (ilvN) is a short protein of 96 amino acid residues (half the size of ilvH and other typical bacterial RSUs) [9,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…17 Heterologous interaction has been detected between E. coli AHAS I and AHAS III in our previous study 18. Furthermore, ilvM (RSU of E. coli AHAS II) is able to activate the CSUs of all three AHAS isozymes from E. coli , and truncated ilvH (AHAS III) can activate the CSUs of both AHAS I and AHAS III 19. These results imply that there might be a common contact surface in the three isozymes of AHASs from E. coli.…”
Section: Introductionmentioning
confidence: 67%